The Effect Of Maternal Fetal Attachment Health Education With Video On Achievement Of Mother's Role In Sleman Primary Health Care - desi sariyani (NHM PRESS, 2020)
Achieving the role of the mother can begin from the beginning of pregnancy until 6 months postpartum. Unpreparedness to achieve the role of motherhood will affect anxiety during pregnancy and after childbirth, violence, child abuse and neglect of care. The purpose of this study was to determine the effect of maternal health education in fetal attachment with audiovisual media on the achievement of the role of mothers in the Sleman Public Health Center. This study uses a quasi-experimental method with the design of the treatment group and the control group. The sample in this study were pregnant women who came to have a pregnancy check up at the Sleman Public Health Center and were divided into two groups, namely the intervention group and the control group where each group numbered 23 respondents. The analysis in this study uses the Wilcoxon Signed Rank Test and Mann-Whitney. The results showed that the use of audiovisual media is better than conventional methods because it has a value of an average difference after the provision of higher health education.